Flow-weighted sourcing of freshwater runoff from Pacific-draining continental and coastal basins in south-western Patagonia (41-56° S): characterizing regional inputs to Chilean fjords - Moreno-Meynard, Paulo; Artal, Osvaldo; Torres, Rodrigo; Reid, Brian (Frontiers in Marine Science, 2024)
Global estimates of the supply of dissolved and suspended materials to the ocean, in order to be relevant at either political or ecological scales, belie a finer-scale analysis necessary for understanding specific terrestrial-marine interactions. This is especially true for continental runoff to the marine critical zone of inland fjords and channels, where mechanisms, drivers, and predictions need to be elaborated in the context of changing land use and shifting climate forcing. In fjords in south-western Patagonia, runoff from small coastal and large continental basins ( 310 x103 km2), sourced from a diverse geography and wide climatic gradient (<150 – 6,000+ mm/year), correspond with a very low density of hydrological and water quality observations. Based on the recently developed regional runoff model (FLOW), we estimated the coastal freshwater discharges and characterized flow-weighted sourcing (land use-cover type, climate, glaciers/geology, and soil province) for Pacific drainages from 41° to 56° south latitude. An estimated 692 km3/year (mean across 1979-2018), or 2% of worldwide total, is more than 85% of previous estimates for the much larger Pacific South American input. Based on limited water quality observations and inference from runoff sourcing, we predict general patterns of export for four groups of continental resources important for marine productivity, including: significant regional variation in flow seasonality, a N-S gradient in declining input of silicic acid and increased glacial input of sediment and iron, and potential shift in dissolved organic matter input sources from rainforest (potentially labile) to peatlands (refractory). Finally, we emphasize the temporal and spatial consequences of near-reference condition river runoff for marine ecosystem productivity and function in the Patagonian fjords, with specific recommendations for water quality standards and sustained monitoring for coupled river and marine ecosystems.